Real-time hiring of vehicles for container transport - Evers, Joseph J.M. (European Journal of Transport and Infrastructure Research, 2006)
This study concerns the deployment of large numbers of container transporting vehicles on a network consisting of (dedicated) roads and logistic sites such as container terminals. Each site is managed autonomously by a site manager. The fleet of vehicles is deployed by a fleet manager. On request of the site managers, the fleet manager allocates vehicles to be hired by the site managers. Next, within these allocations, each site manager issues transportation jobs and assigns these jobs to the allocated vehicles. The objective of the fleet manager is to avoid unpaid empty driving and to keep the size of its fleet just large enough the serve the demand for vehicles. The objective of the site managers is to minimize the operational costs. In this context a new coordination system is proposed to allocate vehicle capacity, operating on the basis of a win-win situation for all actors. The coordination takes place at two levels. One level concerns the drawing up of an adaptive fleet deployment plan. The other level resides under control of the individual site managers and concerns the assignment of transportation jobs to vehicles, given the allocations of the fleet deployment plan. Both use repetitive linear programming procedures. Small size simulation experiments show that the approach might be effective.